WORKSHOP PEMANFAATAN TANAMAN KOPI BERJENIS ROBUSTA MENJADI BUBUK KOPI ROBUSTA DAN TEH CASCARA SEBAGAI UPAYA MENGOPTIMALKAN PRODUKTIFITAS UMKM DESA BAYAN - Sasongko, Sudi Mariyanto Al; Darmawan, Lalu Sukma; Nafisah, Mufrihatun; Noviana, Yulia; Misnawati, Misnawati; Wahyuni, Astriana; Cahyani, Armita Dwi; Agustira, Mislahul Ihsan; Sujiwo, Teguh Maulana; Zulkipli, Muhammad Zidane Athaya; Halimatussakdiah, Halimatussakdiah (Jurnal Wicara, 2024)
Bayan Village, located in Bayan District, North Lombok Regency, West Nusa Tenggara Province, has great potential in the agricultural and plantation sectors due to its strategic location at the foot of Mount Rinjani. The fertile soil in this village allows residents to grow various crops, including coffee. However, most residents only sell coffee in raw form without going through the processing process, so the added value of coffee products is not optimal. To overcome this, a workshop was held on processing robusta coffee into robusta coffee powder and cascara tea as an effort to optimize the productivity of MSMEs in Bayan Village. This workshop aims to increase the productivity of MSMEs by processing coffee into high-value products. In addition to increasing economic value, this workshop is also expected to reduce coffee skin waste in Bayan Village and provide additional sources of income for residents. Thus, Bayan Village can be an example of a village that has succeeded in optimally utilizing its natural potential, creating new jobs, increasing residents' income and contributing to sustainable village economic growth.